Miocene organic-rich layers of the Saouef Formation (Oriental Tunisia); insights into temporal and spatial variability of environmental conditions during deposition. (October 2022) - Radhwani, Malek; Singh, Vikram P.; Bechtel, Achim; Singh, Bhagwan D.; Mannaï-Tayech, Beya
Highlights: The organic-rich layers of the Saouef Formation are considered as fair to good gas-prone sources. Molecular and petrographic data argue for deposition within an alluvial coastal plain. Terpenoid biomarkers reveal highly variable contributions of conifers and angiosperms to peat formation. Recurring forest or mire fires are evidenced. Regional differences in depositional environment are outlined based on outcrop data. Abstract: Miocene organic-rich sediments (coal and carbonaceous clays) from the La Falaise section of the Saouef Formation have been investigated by organic petrographic, palynofacies and organic geochemical approaches. The results are compared with data obtained during a previous study of the nearby Saouef section. The sedimentary succession is built up by repetitive sedimentary sequences (i.e., parasequences) deposited during progradation and retrogradation, respectively. The coal, or carbonaceous layers, developed during the establishment of clay-dominated sedimentation. The organic-rich layers within the samples, containing high amounts of mineral matter, are dark brown, with a stratified texture and are classified as humic coal. Microscopically, the huminite group dominates the maceral composition of the carbonaceous clays and lignite (av. 75% mmf). The variable degrees of the tissue preservation index (TPI) and highly fluctuating vegetation index (VI) values provide evidence for different contributions of vascular plants vs. herbaceous vegetation and macrophytes, to peat formation. Higher contributions of macrophytes (e.g., reed grasses) to peat accumulation at La Falaise are concluded, based on n -alkane distributions. High mineral matter contents and changing gelification index (GI), and ground water index (GWI) values, found in both sections, provide evidence for rheotrophic hydrogeological conditions, and peat formation within wet forest swamp to inundated marsh environment. The low sulphur contents attest to peat formation within a freshwater environment and the relative proportions of ββ to (ββ + αβ)-C31 hopanes argue for slightly acidic conditions. In comparison to the results of the Saouef section (average pH of 5.6), a lower pH (4.2) is revealed from the average hopane isomerization ratio of the La Falaise samples. The palynofacies investigation of the La Falaise deposits indicates the dominance of phytoclasts over amorphous organic matter (AOM) in most of the samples and suggests good preservation of the higher plant remains. In contrast, increased degradation of plant tissues under oxygen-deficient conditions is concluded from the enhanced proportions of AOM found in several of the previously investigated Saouef samples. The molecular analysis of hydrocarbons from all the samples indicated the dominance of n -alkanes and hopanoids. The obtained pristane/phytane ratios argue for sub-oxic conditions during peatification at La Falaise, whereas data from our previous study of the Saouef section provided evidence for a reducing environment. Terpenoid hydrocarbon compositions reveal highly variable contributions of conifers and angiosperms to peat formation, consistent with previous findings at the Saouef sampling site. The presence of polycyclic aromatic hydrocarbons (PAHs), as well as fusinite, provides evidence for mire or forest fires. The comparison of the results from lignite of both sections of the Saouef Formation indicate comparable, highly variable conditions during peat accumulation, probably governed by eustatic sea level changes. The peatlands most likely developed due to the establishment of flood basins situated between alluvial ridges. The obtained regional differences are suggested to reflect slightly different hydrological conditions and associated vegetation cover in the peatlands.